How to be an academic superhero : establishing and sustaining a successful career in the social sciences, arts and humanities - Hay, Iain (How to guides, 2023)
"This thoroughly revised second edition draws on the author's decades of observations and experiences in academia, providing insight and responding to the challenges of fostering a successful academic career. Written in a clear and concise style, the book provides fully updated, forthright and practical counsel on achieving and maintaining a successful, balanced career amidst today's intensifying institutional needs and demands. Iain Hay offers a deep understanding of academic career development from PhD to retirement and in this book addresses a wide range of areas such as writing compelling job applications, handling job offers, academic networking, preserving your public reputation, working with research teams, and how to undertake productive sabbatical leave. The breadth of coverage in this updated book ensures that it will be an excellent resource not only for students and early career academics striving to understand how to establish and cultivate an excellent career path, but also to more senior scholars who are mentoring post graduate students and junior colleagues whilst working to sustain their own careers"--